2013
DOI: 10.1037/a0031949
|View full text |Cite
|
Sign up to set email alerts
|

The medial preoptic area modulates cocaine-induced activity in female rats.

Abstract: Drugs of abuse exert their effects by exploiting natural neurobiological reward mechanisms, especially the mesolimbic dopamine (DA) system. However, the mesolimbic system does not operate in isolation, and input from other reward-relevant structures may play a role in cocaine’s rewarding effects. The medial preoptic area (mPOA) of the hypothalamus is involved in the regulation of two essential and naturally rewarding behaviors, sexual and maternal behaviors. It also makes strong neuroanatomical connections wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

15
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 81 publications
15
42
0
Order By: Relevance
“…Similarly, as the mPOA is essential for sexual [11] and maternal behaviors [12], contains one of the highest concentrations of cells expressing sex-steroid hormone receptors [13], and contains robust connections with the mesolimbic system [14], it is not surprising that it should also modulate cocaine-induced behavioral activity. Dopamine in the NAc increases locomotion [2, 3], removing a source of inhibition into the mesolimbic dopamine system, namely the mPOA [8, 9], should then facilitate locomotion, as is evidenced in our present findings. However, how the mPOA achieves this modulation is not entirely clear.…”
supporting
confidence: 64%
See 4 more Smart Citations
“…Similarly, as the mPOA is essential for sexual [11] and maternal behaviors [12], contains one of the highest concentrations of cells expressing sex-steroid hormone receptors [13], and contains robust connections with the mesolimbic system [14], it is not surprising that it should also modulate cocaine-induced behavioral activity. Dopamine in the NAc increases locomotion [2, 3], removing a source of inhibition into the mesolimbic dopamine system, namely the mPOA [8, 9], should then facilitate locomotion, as is evidenced in our present findings. However, how the mPOA achieves this modulation is not entirely clear.…”
supporting
confidence: 64%
“…Our findings demonstrated that neurotoxic lesions of the medial preoptic area (mPOA) increased cocaine-induced dopamine release in the NAc, that many of the neurons projecting from the mPOA to the ventral tegmental area (VTA) are sensitive to estradiol, and that estradiol microinjections into the mPOA 24-hours prior to cocaine administration increased cocaine-induced dopamine release in the NAc [9]. These results are in line with additional work from our laboratory revealing that lesions of the mPOA enhanced cocaine-induced conditioned place preference (CPP) and cocaine-induced cellular activity in the NAc [8]. Together, these results point to the mPOA as an integral region in the processing of cocaine-induced response.…”
supporting
confidence: 53%
See 3 more Smart Citations